Signal peptide exchange for higher expression of Bjerkandera adusta Loosenin 1 in P. pastoris - Brinkenstråhle, Linus (SLU/Department of Molecular Sciences, 2018)
The protein Loosenin 1 from the wood degrading fungus Bjerkandera adu-sta (BaLOOS1) has been shown to loosen up recalcitrant biomass and en-hance enzymatic saccharification. BaLOOS1 is the only loosenin protein that has been biochemically characterised so far. An earlier attempt to ex-press BaLOOS1 in Pichia pastoris, with its native signal peptide (SP), indi-cated low expression level (T. Haataja and J. Ståhlberg, unpublished).